2023
DOI: 10.1128/iai.00432-22
|View full text |Cite
|
Sign up to set email alerts
|

Sound the (Smaller) Alarm: The Triphosphate Magic Spot Nucleotide pGpp

Abstract: It has recently become evident that the bacterial stringent response is regulated by a triphosphate alarmone (pGpp) as well as the canonical tetra- and pentaphosphate alarmones ppGpp and pppGpp [together, (p)ppGpp]. Often dismissed in the past as an artifact or degradation product, pGpp has been confirmed as a deliberate endpoint of multiple synthetic pathways utilizing GMP, (p)ppGpp, or GDP/GTP as precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 93 publications
(222 reference statements)
0
4
0
Order By: Relevance
“…A previous study has shown that NCBP2 can mediate gene interactions to modify neurodevelopmental defects of the 3q29 deletion ( 52 ). Additionally, nudix hydroxylases (NUDTs) belong to the versatile, widely distributed, housecleaning enzyme family to catalyze the hydrolysis of a wide range of nucleoside pyrophosphates linked to amino acids ( 53 , 54 ). Furthermore, previous researches have reported that NUDT10 expression is associated with malignant behaviors of gastric cancer by promoting tumor cell invasion and a poor prognosis ( 55 , 56 ), whereas NUDT11 has been shown to be associated with longer survival period in liver cancer ( 57 ) and bladder cancer ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that NCBP2 can mediate gene interactions to modify neurodevelopmental defects of the 3q29 deletion ( 52 ). Additionally, nudix hydroxylases (NUDTs) belong to the versatile, widely distributed, housecleaning enzyme family to catalyze the hydrolysis of a wide range of nucleoside pyrophosphates linked to amino acids ( 53 , 54 ). Furthermore, previous researches have reported that NUDT10 expression is associated with malignant behaviors of gastric cancer by promoting tumor cell invasion and a poor prognosis ( 55 , 56 ), whereas NUDT11 has been shown to be associated with longer survival period in liver cancer ( 57 ) and bladder cancer ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SR is controlled by the accumulation of intracellular alarmone nucleotides that are collectively known as (pp)pGpp (9, 10). These alarmones are metabolized by bifunctional synthetase/hydrolase enzymes from the RSH or Rel (RelA/SpoT homology) family, monofunctional small alarmone hydrolases (SAH), and monofunctional small alarmone synthetases (SAS) (11).…”
Section: Introductionmentioning
confidence: 99%
“…The highly conserved synthetase domains of RSH and SAS enzymes transfer a pyrophosphate from ATP to the 3’ OH of guanosine nucleotide precursors. Typically, the utilization of GMP, GDP, or GTP results in the synthesis of pGpp, ppGpp, or pppGpp, respectively (9, 10). C. difficile encodes highly conserved RSH and RelQ homologs whose alarmone synthesis contributes to antibiotic survival (10, 14, 15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SR is controlled by the accumulation of intracellular alarmone nucleotides that are collectively known as (pp)pGpp [9,10]. These alarmones are metabolized by bifunctional synthetase/hydrolase enzymes from the RSH or Rel (RelA/SpoT homology) family, monofunctional small alarmone hydrolases (SAHs), and monofunctional small alarmone synthetases (SASs) [11].…”
Section: Introductionmentioning
confidence: 99%